Survival Trends and Long-Term Toxicity in Pediatric Patients with Osteosarcoma. (25th November 2012) - Hagleitner, Melanie M.; de Bont, Eveline S. J. M.; te Loo, D. Maroeska W. M.
Abstract : Background . This study was conducted to investigate the clinical characteristics and treatment results of osteosarcoma in pediatric patients during the past 30 years. Trends in survival rates and long-term toxicity were analyzed. Procedure . 130 pediatric patients under the age of 20 years with primary localized or metastatic high-grade osteosarcoma were analyzed regarding demographic, treatment-related variables, long-term toxicity, and survival data. Results . Comparison of the different time periods of treatment showed that the 5-year OS improved from 58.6% for children diagnosed during 1979–1983 to 78.6% for those diagnosed during 2003–2008 (P = 0.13 ). Interestingly, the basic treatment agents including cisplatin, doxorubicin, and methotrexate remained the same. Treatment reduction due to acute toxicity was less frequent in patients treated in the last era (7.1% versus 24.1% in patients treated in 1979–1983;P = 0.04 ). Furthermore, late cardiac effects and secondary malignancies can become evident many years after treatment. Conclusion . We elucidate the prevalence of toxicity to therapy of patients with osteosarcoma over the past 30 years. The overall improvement in survival may in part be attributed to improved supportive care allowing regimens to be administered to best advantage with higher tolerance of chemotherapy and therefore less chemotherapy-related toxicity.